The impact of physical activity on the mental health of university students: An epidemiological study from Paraguay - Torales Julio; Di Giuseppe Matías Franco; Almirón-Santacruz Marcos; O’Higgins Marcelo; Amarilla Diego; Caycho-Rodríguez Tomás; Ventriglio Antonio; Castaldelli-Maia João Mauricio; Barrios Iván (Biomedical Human Kinetics, 2024)
Study aim: This study aimed to investigate the impact of physical activity on the mental health characteristics of a sample of university students from Paraguay, assessing their daily physical activity and the prevalence of depression, anxiety, and stress.